2013
DOI: 10.1080/02757540.2012.735659
|View full text |Cite
|
Sign up to set email alerts
|

The gastropodOsilinus atrataas a bioindicator of Cd, Cu, Pb and Zn contamination in the coastal waters of the Canary Islands

Abstract: The aim of this study was to assess the use of Osilinus atrata (Gastropoda, Mollusca) as a biomonitor of heavy metals (Cd, Cu, Pb and Zn) within the coastal zone of the Canary Islands. In general, this top-shell snail showed high intraspecific variability in its tissue metal concentrations, which decreased according to the following sequence: Cu ≥ Zn > Cd ≥ Pb. In particular, Cd and Zn concentrations were higher in males than in females, whereas Cu concentrations increased slightly with weight, and Pb concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Nonessential heavy metals have no known biological role in living organisms. Examples of essential heavy metals are Mn, Fe, Cu, and Zn, while the heavy metals Cd, Pb, and Hg are toxic and are regarded as biologically nonessential [18][19][20][21]. e heavy metals Mn, Fe, Co, Ni, Cu, Zn, and Mo are micronutrients or trace elements for plants.…”
Section: Essential and Nonessential Hmsmentioning
confidence: 99%
“…Nonessential heavy metals have no known biological role in living organisms. Examples of essential heavy metals are Mn, Fe, Cu, and Zn, while the heavy metals Cd, Pb, and Hg are toxic and are regarded as biologically nonessential [18][19][20][21]. e heavy metals Mn, Fe, Co, Ni, Cu, Zn, and Mo are micronutrients or trace elements for plants.…”
Section: Essential and Nonessential Hmsmentioning
confidence: 99%
“…Other heavy metals that have no biological role are called nonessential heavy metals such as lead. 2 Melting and oxidizing zinc at high temperature can generate one of the most widely used nanoparticles (NPs) in the world, which is ZnO-NPs. 3,4 Currently, ZnO-NPs are widely applied in medicine as antibacterial, fungicidal, anticancer.…”
mentioning
confidence: 99%
“…Furthermore, Fe 3 O 4 NPs have likewise known enzymes activators similar isocitratelyase which consumed by the microbial cells throughout microbes growth on the hydrophobic substrate, in addition to throughout acetyl-CoA incorporation into C4 complexes or throughout the bio-surfactant synthesis [61,62]. Many studies [63][64][65][66] were reported that heavy metals were significant for bionics besides might be required by the body in moderately little concentrations. For example, the vital heavy metals (Mn, Fe, Co, Ni, Mo, Cu, and Zn) were micronutrients otherwise trace elements for microbial organisms [67].…”
Section: Influence Of Different Concentrations Of Prepared Fe 3 O 4 Nps On the Microbial Growthmentioning
confidence: 99%